New transferable electronic cash scheme - XU Guo-sheng1; GU Li-ze1; YANG Yi-xian1; LI Zhong-xian1 (Tongxin xuebao)
A new transferable off-line e-cash scheme was proposed. By an introduction of a new restrictive blind signa-ture,restrictive blindness of user’s identity is implemented,by an introduction of ID-based public key system,a multi-proxy signature,and then the untraceability of user’s e-cash,is implemented. Otherwise,the scheme has an advan-tage of the detection of double spending,in which double spender can be revealed directly.